A comparative analysis of the substance use and mental health characteristics of nurses who complete suicide. Issue 13 (25th March 2021) - Choflet, Amanda; Davidson, Judy; Lee, Kelly C.; Ye, Gordon; Barnes, Arianna; Zisook, Sidney
Abstract: Aims and objectives: To describe the substance use and mental health characteristics of nurses who complete suicide compared to non‐nurses. Background: Nurses are at higher risk of suicide than the general population. The relationship between substance use, mental health and suicide in a large sample of nurses in the USA has not been previously described. Design: Retrospective observational quantitative analysis. Methods: Suicide data were retrospectively analysed in the Centers for Disease Control and Prevention National Violent Death Reporting System from 2003 to 2017. Data were compared between nurses who died by suicide (n = 2, 306) and non‐nurses who died by suicide (n = 185, 620) using odds ratios calculations and chi‐square test of proportions to detect independent risk factors of suicide completion in nurses. This study followed the STROBE guidelines. Results: Significant differences between nurses and non‐nurses were found. Among decedents for whom substances were implicated as a cause of death, nurses were far more likely to be positive at the time of death for almost all substance classifications. Both male and female nurses were more likely than non‐nurses to have a mental health problem reported. Among both female and male nurses, job problems were more prevalent compared to non‐nurses (12.8% and 19.9% versus 7.2% and 11.9%, respectively). Female nurses were more likely to have a physical health problem compared to female non‐nurses, male nurses and male non‐nurses (26.2% versus 21.3%, 22% and 20.4%). Conclusion: Unique relationships between substance use and mental health exist among nurses who complete suicide which may offer specific opportunities for interventions to reduce suicide. Relevance to Clinical Practice: Efforts to address workplace stress, facilitate self‐referral for risky substance use, encourage mental health treatment and reduce the stigma associated with seeking help all offer potential interventions to reduce nurse suicide.